Telaah Kritis terhadap Pendekatan Ekoteologi dalam Upaya Pelestarian Hewan Liar di Minahasa - Glenn Allen Tielung; Tony Rudyansjah (Antropologi Indonesia, 2019)
The environmental theology approach, known as ecotheology, attempts to make people aware of their actions towards the natural environment through a theological framework. Its basic assumption departs from the idea that the dogma of hierarchical construction of the universe is the dominant factor in influencing ethical relation between humans and the natural world surrounding them. Within the framework of the dogma, humans are given a special mandate to maintain other creations. This article argues that ecotheology’s approach in conserving wild animals in Minahasa is still trapped in the ontological model of dualism. It is characterized by humans’ special status compared to other creations. It has the potential to negate other ethical choices that depart from different ontological models. Therefore, this approach will find it difficult to answer the question of why in on ontological model there are two contradictory ethical actions: on the one side, conservation, and on the other, exploitation. As an alternative, ecotheology first needs to understand the complexities of human motivation and action and then abstract it within theological framework.